Highly-sensitive epinephrine sensors based on organic electrochemical transistors with carbon nanomaterial modified gate electrodes1. Issue 25 (7th July 2015) - Mak, Chun Hin; Liao, Caizhi; Fu, Ying; Zhang, Meng; Tang, Chun Yin; Tsang, Yuen Hong; Chan, Helen L. W.; Yan, Feng
<x xml:space="preserve">Abstract</x> The sensitivity of OECT-based epinephrine sensors has been dramatically improved by modifying carbon nanomaterials on the Pt gate electrodes.